Angiofibroma do septo nasal: Uma apresentação extremamente rara - Fernandez Martinez; Diaz Argüello; Maseda Alvarez; . Calzada (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Angiofibromas are well-documented tumours occurring almost exclusively in adolescent boys. They are morphologically benign but can be locally aggressive and destructives. Although most angiofibromas originate in the nasopharynx, they are not limited to this region. They can involve the nose, paranasal sinuses and cranium, although primary extranasopharyngeal sites are rare. We report a septal angiofibroma, an extremely unusual presentation, in a 54-year old patient. To date only seven reports have been described in the literature. We discuss the differential diagnosis, and treatment.